Pengembangan Media Buku Bergambar Berbasis Kearifan Lokal Sasak pada Mata Pelajaran Pendidikan Pancasila Kelas IV Sekolah Dasar Negeri 1 Akar-Akar - Istinathul Fitrah Ramdhani Putri; Khairun Nisa; Muhammad Sobri (Mataram University, 2026)
This study aimed to develop a picture book learning medium based on Sasak local wisdom and determine its validity, practicality, and effectiveness in Pancasila Education for fourth-grade students at State Elementary School 1 Akar-Akar. This study employed a Research and Development method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The participants were 25 fourth-grade students. Data were collected through material expert and media expert validation questionnaires, teacher and student response questionnaires, learning achievement tests, and documentation. The data were analyzed using validity and practicality percentages, a paired-samples t-test, and the N-Gain test. The results showed that the material expert validation reached 82% and the media expert validation reached 84%, both of which were categorized as highly valid. The teacher response reached 95%, while the student response reached 95.1%, both of which were categorized as highly practical. The students’ mean score increased from 47.40 on the pretest to 91.40 on the posttest. The t-test result showed that the calculated t-value of 15.24 was higher than the critical t-value of 2.064, with a significance level of less than 0.001. The average N-Gain score was 0.86 or 85.88%, indicating a high and effective improvement. Therefore, the Sasak local wisdom-based picture book was highly valid, highly practical, and effective in improving fourth-grade students’ learning outcomes and understanding of Pancasila values.